Extracellular nuclease from a thermophile, streptomyces thermonitrificans: production, purification and partial characterization of - double strand preferential - deoxyribonuclease activity - Patil, N. S.; Deshmukh, Satej S.; Shankar, V. (Process Biochemistry, 2005)
A thermophilic strain of Streptomyces themionitrificans produced high levels of extracellular nuclease (designated as nuclease Stn beta) when grown on nutrient broth glucose medium. Maximal nuclease activity (51 U ml(-1)) was obtained, in 40 h, when the culture was grown on modified NBG medium at 45 degreesC. The enzyme was purified to homogeneity with an overall recovery of 5.6% and a specific activity of 10,833. The relative molecular mass of the purified enzyme, determined by gel filtration, was 22.4 kDa and it showed an obligate requirement for Mn2+ for activity. The optimum pH and temperature of nuclease Stn beta were 8.0 and 45 degreesC, respectively. The enzyme was inhibited by Mg2+ CO2+, Cu2+, Zn2+ and Hg2+, inorganic phosphate, pyrophosphate, dithiothreitol, beta-mereaptoethanol, EDTA and NaCl. Nuclease Stn beta was stable to high concentrations of urea and organic solvents but susceptible to low concentrations of SDS and guanidine hydrochloride. Nuclease Stn beta is a multifunctional enzyme with substrate specificity in the order of dsDNA > ssDNA much greater than RNA. The end products of dsDNA hydrolysis were predominantly oligonucleotides (85-90%) and small amounts of 5' mononucleotides (10-15%) suggesting an endo mode of action. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Characterization; Endonuclease; extracellular nuclease; production; Purification; Streptomyces thermonitrificans

Nuclease Stn alpha from Streptomyces thermonitrificans: characterization of the associated adenylic acid preferential ribonuclease activity - Deshmukh, Satej S. (Current Microbiology, 2007)
Nuclease Stn alpha from Streptomyces thermonitrificans hydrolyses DNA and RNA at the rate of approximately 10:l. The optimum pH and temperature for RNA hydrolysis were 7.0 and 45 degrees C. The RNase activity of nuclease Stn alpha had neither an obligate requirement of metal ions nor was it activated in the presence of metal ions. The enzyme was inhibited by Zn2+, Mg2+, Co2+, and Ca2+; inorganic phosphate; pyrophosphate; NaCl; KCl; and metal chelators. It was stable at high concentrations of urea but susceptible to low concentrations of Sodium dodecyl sulfate and guanidine hydrochloride. The rates by which nuclease Stn alpha hydrolysed polyribonucleotides occurs in the order of poly A >> RNA >> poly U > poly G > poly C. The enzyme cleaved RNA to 3' mononucleotides with preferential liberation of 3'AMP, indicating it to be an adenylic acid preferential endonuclease.

Pd-Phosphinesulfonate bravely battles the ``vinyl halide insertion copolymerization'' barricade - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2014)
This overview provides insights into the current state-of-the-art solutions to insertion copolymerization of functional olefinic monomers. The challenges in insertion copolymerization of functional olefinic monomers, with a special emphasis on vinyl halides, are highlighted. The crucial design of the Pd-phosphinesulfonate [Pd(PO)] enables up to 3.6 mol % incorporation of vinyl fluoride (VF) in an ethylene-VF copolymerization reaction. In a significant development, insertion copolymerization of industrially relevant functional olefin, that is, vinyl chloride (VC), was unambiguously ascertained, and a detectable amount of VC (0.4 mol %) was incorporated (at the chain end). In a detailed investigation, the in situ existence of (PO)PdH species during the polymerization was revealed, and it was demonstrated that these are indeed responsible for VC incorporation. (c) 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1-6
Keywords: functional olefin; insertion copolymerization; palladium catalyst; phosphinesulfonate; vinyl chloride

Insertion copolymerization of difunctional polar vinyl monomers with ethylene - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Chikkali, Samir H. (ACS Macro Letters, 2015)
A single-step synthesis, structural characterization and application of a neutral, acetonitrile ligated, palladium-phosphinesulfonate complex [{P<\^>O}PdMe(L)] (P<\^>O = K-2-P,O Ar2PC6H4SO2O with Ar = 2-MeOC6H4; L = CH3CN) (3) in coordination/insertion copolymerization of ethylene with difunctional olefin is investigated. In a significant development, complex 3 was found to catalyze insertion copolymerization of industrially relevant 1,1-disubstituted difunctional vinyl monomers for the first time. Thus, insertion copolymerization of ethyl-2-cyanoacrylate (ECA or super glue) and trifluoromethyl acrylic acid (TFMAA) with ethylene produced the corresponding copolymers with 6.5% ECA and 3% TFMAA incorporation. Increasing the concentration of difunctional olefins led to higher incorporation but at the expense of lower activities. These observations indicate that complex 3 tolerates difunctional vinyl monomers and provides direct access to difunctional polyolefins that have not been attempted before.

Reactivity of difunctional polar monomers and ethylene copolymerization: a comprehensive account - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Koshti, Vijay S.; Poddar, Suparna; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Chikkali, Samir H. (Macromolecules, 2017)
A comprehensive picture of insertion of 1,1-disubstituted difunctional olefins, their ability to double the functional group density at the same level of incorporation as that of monofunctional olefin, and copolymerization with ethylene has been demonstrated. Exposure of a palladium complex [P boolean AND OPdMe(L)] (P boolean AND O = kappa(2)-P,O-Ar2PC6H4SO2O with Ar = 2-MeOC6H4.; L = C2H6OS) to methyl 2-acetamidoacrylate (MAAA) revealed slight preference for 1,2-insertion over 2,1-insertion (1.0:0.7). In contrast, insertion of electron-deficient 2-(trifluoromethyl)acrylic acid (TFMAA) unveiled selective 2,1-insertion {via [(P boolean AND O)PdC5H6F3O2] (11)1. The unstable intermediate 11 undergoes beta-hydride and beta-fluoride elimination to produce subsequent insertion and elimination products. The identity of elimination products (E/Z)-2-trifluoromethyl)but-2-enoic acid [17(E/Z)] and 2-(difluoromethylene)butanoic acid (13) was fully established by 1-2D NMR spectroscopy. These insertion experiments, taken together with insertion rates, suggest that MAAA and TFMAA. are amenable to insertion. Polymerization of ethylene with MAAA, TFMAA, acetamidoacrylic acid, 2-bromoacrylic acid, dimethyl allylmalonate, and allylmalonic acid was catalyzed by [P boolean AND OPdMe(L)] (L = C2H3N) (S.ACN), and the highest incorporation of 11.8% was observed for dimethyl allylmalonate (DMAM). The changes in the surface properties of the copolymers after incorporation of difunctional olefins were evaluated by measuring the water contact angle. Copolymer with highest (11.8% of DMAM) incorporation revealed a reduced water contact angle of 76 degrees. These findings demonstrate that 1,1-disubstituted difunctional olefins are amenable to polymerization, and incorporation of difunctional olefins In polyethylene backbone leads to the production of relatively hydrophilic polyethylene copolymers.

Secondary interactions arrest the hemiaminal intermediate to invert the modus operandi of schiff base reaction: a route to benzoxazinones - Patel, Ketan; Deshmukh, Satej S.; Bodkhe, Dnyaneshwar; Mane, Manoj; Vanka, Kumar; Shinde, Dinesh; Rajamohanan, Pattuparambil R.; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Chikkali, Samir H. (Journal of Organic Chemistry, 2017)
Discovered by Hugo Schiff, condensation between amine and aldehyde represents one of the most ubiquitous reactions in chemistry. This classical reaction is widely used to manufacture pharmaceuticals and fine chemicals. However, the rapid and reversible formation of Schiff base prohibits formation of alternative products, of which benzoxazinones are an important class. Therefore, manipulating the reactivity of two partners to invert the course of this reaction is an elusive target. Presented here is a synthetic strategy that regulates the sequence of Schiff base reaction via weak secondary interactions. Guided by the computational models, reaction between 2,3,4,5,6-pentafluoro-benzaldehyde with 2-amino-6methylbenzoic acid revealed quantitative (99%) formation of 5-methyl-2-(perfluoropheny01,2-dihydro-4H-benzo[d][1,3]oxazin-4-one (15). Electron donating and electron withdrawing ortho-substituents on 2-aminobenzoic acid resulted in the production of benzoxazinones 936. The mode of action was tracked using low temperature NMR, IN vis spectroscopy, and isotopic (O-18) labeling experiments. These spectroscopic mechanistic investigations revealed that the hemiaminal intermediate is arrested by the hydrogen-bonding motif to yield benzoxazinone. Thus, the mechanistic investigations and DFT calculations categorically rule out the possibility of in situ imine formation followed by ring-closing, but support instead hydrogen-bond assisted ring-closing to prodrugs. This unprecedented reaction represents an interesting and competitive alternative to metal catalyzed and classical methods of preparing benzoxazinone.

Synthesis of meta-substituted monodentate phosphinite ligands and implication in hydroformylation - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Pandey, Swechchha; Mali, Pramod S.; Chikkali, Samir H. (Journal of Chemical Sciences, 2017)
Synthesis of meta-substituted phosphinite ligands 3,3'-(methoxyphosphanediyl) bis(N, N-diethylaniline) (4a) and methoxybis(3-methoxyphenyl) phosphane (4b), in high yields, has been demonstrated. Typical phosphorus chemical shift between 110-120 ppm, appearance of methoxy protons and corresponding carbon, as well as ESI-MS spectra unambiguously confirmed the existence of phosphinite ligands 4a and 4b. To demonstrate the synthetic usefulness of 4a and 4b, these ligands were tested in the rhodium catalyzed hydroformylation of 1-octene. The diethylamine substituted ligand 4a was found to be highly active, whereas 4bwas less reactive but revealed slightly better regioselectivity of 62% under optimized conditions. Additionally, 4a and 4b were found to catalyze the hydroformylation of styrene, 1-undecenol and 1,1-disubstituted functional olefin, methyl methacrylate. Both the ligands displayed excellent conversion of styrene, and 4b revealed an excellent branch selectivity of 75%. Although 1-undecenol proved to be amenable to hydroformylation (85-90% conversion to aldehyde), both the ligands failed to discriminate between the linear and branched products. Substrate methyl methacrylate proved to be highly challenging and reduced conversion (between 33-42%) was observed under optimized conditions. Ligand 4a was found to be highly selective towards linear aldehyde (81% linear selectivity).

Neutral imino-methyl benzenesulfonate-ligated Pd(II) complexes and implications in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Mote, Nilesh R.; Manod, M.; Gonnade, Rajesh G.; Chikkali, Samir H. (ACS Omega, 2019)
A reaction between sodium 2-formylbenzenesulfonate and aniline revealed the near-quantitative (91%) formation of sodium-2-((phenylimino)methyl)benzenesulfonate L1. The identity of L1 was unambiguously ascertained using spectroscopic and analytical methods. The scope of this methodology was widened and various electron-donating amines were treated with sodium 2-formylbenzenesulfonate, and a small library of 6 imine ligands L2-L6 was generated. When L2 was treated with [(COD)PdMeCI], instead of the anticipated [L2PdMe(DMSO)] complex, the formation of [(DMSO)(2)Pd2Cl2Me2] Pd Dim was observed. Nevertheless, the desired imino-methyl benzenesulfonate-ligated palladium complex [L2PdMe(Lu)] C1 was obtained by in situ abstraction of chloride and addition of bulky 2,6-lutidine as the donor group. The observation of characteristic Pd-Me protons at 0.06 ppm and the corresponding carbon at -8.1 ppm indicated the formation of C1. These 1D NMR observations were corroborated by 2D C-H correlation spectra and mass analysis, and the existence of C1 was unambiguously ascertained. Along the same lines, L4 and L5 were treated with a palladium precursor to produce [L4/SPdMe(Lu)]-type complexes C2-C3 in 55-84% yield, and their identity was established by using a combination of spectroscopic tools, analytical methods, and single-crystal X-ray diffraction. The synthetic utility of C1-C3 has been demonstrated by utilizing these complexes in the insertion polymerization of ethylene to polyethylene.

Palladium-catalyzed insertion of ethylene and 1,1-disubstituted difunctional olefins: an experimental and computational study - Gaikwad, Shahaji R.; Patel, Ketan; Deshmukh, Satej S.; Mote, Nilesh R.; Birajdar, Rajkumar S.; Pandole, Satish P.; Chugh, Jeetender; Chikkali, Samir H. (ChemPlusChem, 2020)
Insertion or coordination copolymerization of ethylene with di-substituted olefins is challenging and the choice of di-substituted mono-functional olefin versus di-substituted di-functional olefin (DDO) appears to be decisive. Here we show that DDO-inserted species are amenable to ethylene insertion and polymerization. DDOs such as 2-acetamidoacrylic acid (AAA), methyl 2-acetamidoacrylate (MAAA), and ethyl 2-cyanoacrylate (ECA) were treated with palladium complex [P perpendicular to OPdMe(L)] (P perpendicular to O=kappa(2)-P,O-Ar2PC6H4SO2O with Ar=2-MeOC6H4; L=C2H6OS) and the existence of respective insertion intermediates in moderate yield (up to 37 %) was established. These intermediates were exposed to ethylene and corresponding ethylene-inserted products were isolated and characterized. A careful comparison with three model compounds confirmed ethylene insertion and polymerization. Thus, the combined experimental and computational investigations show that DDO-inserted species can undergo ethylene insertion and polymerization.
Keywords: Homogeneous catalysis; insertion copolymerization; Olefins; Palladium; Polyethylene

Pd-iminocarboxylate complexes and their behavior in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Gonnade, Rajesh G.; Pandole, Satish P.; Chikkali, Samir H. (Chemistry-An Asian Journal, 2020)
Designing co-catalyst-free late transition metal complexes for ethylene polymerization is a challenging task at the interface of organometallic and polymer chemistry. Herein, a set of new, co-catalyst-free, single-component catalytic systems for ethylene polymerization have been unraveled. Treatment of anthranilic acid with various aldehydes produced four iminocarboxylate ligands (L1-L4) in very good to excellent yield (75-92 %). The existence of 2-((2-methoxybenzylidene)amino) benzoic acid (L1) has been unambiguously demonstrated using NMR spectroscopy, MS and single-crystal X-ray diffraction. A neutral Pd-iminocarboxylate complex [N OPdMe(L1)] (N O=kappa(2)-N,O-ArCHNC6H4CO2 with Ar=2-MeOC6H4) C1 was prepared by treating stoichiometric amount of L1.Na with palladium precursor. The identity of C1 was confirmed by 1-2D NMR spectroscopy and single-crystal X-ray diffraction studies. Along the same lines, palladium complexes C2-C4 were prepared from ligands L2-L4 respectively. In-situ high-pressure NMR investigations revealed that these Pd complexes are amenable to ethylene insertion and undergo facile beta-H elimination to produce propylene. These palladium complexes were then evaluated in ethylene polymerization reaction and various reaction parameters were screened. When C1-C4 were exposed to ethylene pressures of 10-50 bar, formation of low-molecular-weight polyethylene was observed.
Keywords: imine; Imine-carboxylate; Insertion polymerization; Pd complexes; Polyethylene